Small business value chains in local government authorities (LGAs) procurement contracts in Tanzania - Geraldine Arbogast Rasheli (Cogent Business & Management, 2016)
Objective: To assess attitudes toward including small furniture value chains in local government authorities (LGAs) procurement contracts in Tanzania. Methodology: A transaction cost economics theory was used with multiple case study design. Four district executive directors and four small furniture owners were selected purposively. Findings: High transaction costs are experienced by direct actors i.e. both manufactures of furniture and LGAs due to problems associated with furniture manufacturers' characteristics, business capacity, difficulty procedures in public procurement for both pre- and post-contracting stages. Information search costs are high among small furniture value chains participants. Monitoring costs are mainly on waiting time to be paid after delivering furniture among small manufacturers and those associated with small capacity of manufacturers for the case of clients, i.e. LGAs. Upgrading by joining imported furniture and old-fashioned furniture value chains is among the strategies used to reduce both transaction and production costs. Originality: Looks at attitudes toward including local furniture value chains in public procurement contractual process using a transaction costs approach from both potential suppliers and clients. Limitation: Quantitative approaches could not be adopted because there is only a small number of local small-furniture manufacturers participating in public procurement process.
Keywords: 650